ENZYME ACTIVITIES IN TRICHOPHYTON RUBRUM, TRICHOPHYTON MENTAGROPHYTES AND TRICHOPHYTON VERRUCOSUM - F.Zaini (Tehran University of Medical Sciences, 1991)
Since most of the studies on chemical compounds of dermatophytes have shown the existence of a relationship between their pathogenisity and proteolytec enzymes. Activities of 19 different enzymes in viable mycelia and cytoplasmic extracts of T.rubrum (CETr), T.mentagrophytes (CETm) and T.verrucosum (CETv) were investigated by the API-Zym System. The results showed that Viable mycelia of T.rubrm and T.mentagrophytes had valine arylamidase and cystine arylamidase activity where as no such activity was observed in CETr and CETm or in the viable mycelia and cytoplasmic extracts of T.verrucosum. Also the viable mycelia of T.rubrum showed α-mannosidase activity; gowever this enzyme was not detected in CETr, but was active in both the viable mycelia and CETv and CETm. Finally, only in viable mycelia and CETv and CETm was lipase (C14) activity observed. Furthermore none of the viable mycelia of these three species showed any α-galactosidase, β-galactosidase, α-fucosidase,β-glucoronidase, trypsin or chymotrypsin activity.